Implementation barriers and facilitators of a mindfulness‐based social emotional learning program and the role of relational trust: A qualitative study. Issue 8 (6th May 2022) - Mischenko, Polina P.; Nicholas‐Hoff, Pamela; Schussler, Deborah L.; Iwu, Jessica; Jennings, Patricia A.
Abstract: Based on an overarching analysis of the ecological levels or contexts that implementers experienced as barriers and facilitators in the delivery of a mindfulness‐based social‐emotional learning program, this study reveals the importance of relational trust between the implementer and actors within the various ecological levels. This study applies Bryk and Schneider's framework of relational trust to bring nuance and understanding to relationships that influence the implementer's ability to effectively deliver the program. This study explores the implementers' relationships with: the curriculum professional learning team, the district/school administration, schoolteachers/colleagues, students' families, students, and themselves. A qualitative case study approach was employed and included interviews and classroom observations of 10 teachers delivering the program in the elementary school context. Inferences about the strength of relational trust are made between implementers with high and low fidelity based on qualitative and numerical analysis of coded interview segments. Recommendations are made for a whole school community approach that emphasizes the development of relational trust before program implementation. Practitioner points: Implementers' relationships with the Compassionate Schools Project (CSP) professional learning team, district/school, school administrators, school colleagues, students' families, students, and themselves were shown to be integral to implementers' experience delivering the CSP curriculum. High fidelity implementers were more likely to express evidence of strong relational trust between themselves and the key stakeholders than implementers with low fidelity. Low fidelity implementers were more likely to share examples of how they felt unsupported in many of their relationships and how the criteria for relational trust were undermined. Results of this study suggest that the process of developing relational trust among the school community is especially critical for the success of mindfulness‐based programming. We recommend that schools take the time to cultivate the criteria for relational trust before implementing a mindfulness‐based social‐emotional learning (SEL) program for students.